Pendampingan Pembuatan Website Menggunakan CMS untuk Agen Umroh dan Haji AFA Agency - Wiyanto, Wiyanto; Hidayat, Jose Julian; Werdana, Aditya Pratama; Nugroho, Agung; Suwarno, Agus (VINICHO MEDIA PUBLISINDO, 2025)
It is an obligation for lecturers to fulfill the Tridharma of Higher Education, namely education, research, and service. In order to fulfill these obligations, various forms of service to others should be carried out by lecturers and can involve students in the Pelita Bangsa University environment, especially in the Informatics Engineering study program and other study programs so that they can collaborate with each other. The service program carried out is at the Umrah and Hajj service agency Afa Agency which is located at Perum. Bumi Citra Lestari Jl. Cempaka XI, Blok C66 No. 16 Kab. Bekasi. Afa Agency is an Umrah and Hajj agent established in January 2024 which is committed to accompanying your worship to the holy land, which at this time in marketing Umrah and Hajj services using WhatsApp, Facebook, Instagram and other media, and does not yet have a website in marketing its products and services, from this Afa Agency needs a website to make the marketing process easy and widespread. The purpose of this community service is to provide assistance in making a website using CMS to market Umrah and Hajj products and services at Afa Agency. Another benefit of this service is to contribute to the community in the application of science in the computer field. This service is organized using the method of mentoring in making websites assisted by Informatics Engineering study program students